What Are We Waiting For? It’s Time to Regulate Paralegals in Canada - Trabucco, Lisa (Windsor Yearbook of Access to Justice / Recueil annuel de Windsor d'accès à la justice)

(untitled) (Faculty of Law, University of Windsor, 2018)
Law societies in Canada have long been granted the privilege of self-regulation by the state – a privilege that comes with a statutory duty to govern in the public interest. There exists an access to justice crisis in this country. More must be done to address unmet legal needs. There is nothing new in this, but law societies across Canada are reluctant to implement at least one ready solution. Ontario introduced paralegal regulation over ten years ago with the promise that it would increase access to justice. Evidence suggests that it has done so. Yet no other Canadian jurisdiction is prepared to regulate paralegals as independent providers of legal services. Law societies’ continued resistance to the regulation of paralegals is contrary to the public interest. This paper argues that to alleviate the access to justice crisis, it is time to regulate paralegals.